The Philosophy of the Modern Age: The Issue of the Source of Meaningful Presence - Bazaluk, Oleg (Տիգրան Մեծ)
A brief analysis of the philosophy of the Modern Age has allowed establishing the following. (1) The idea of philosophy, formulated by Plato, has hold sway in modern history. It corresponds to the demands of a new reality, which is revealed as a process. (2) In the context of a new reality, the idea of philosophy revealed previously unknown qualities. Martin Heidegger proved that the idea of philosophy does not need Mediators or any other external source. Instead, the unity of certain discourse and way of life has an inner source, which Heidegger coined the term “the appropriated clearing” (die ereignete Lichtung). This source reveals in the idea of philosophy the potency ( ν μ , dúnamis), which under certain conditions is capable of transforming an individual discourse and a way of life independently.
Keywords: Philosophy